Pile Load Testing At JFK International Airport - Synopsis - J. Moskowitz (Deep Foundations Institute, 2000)
Construction of the new JFK International Airport Light Rail System (LRS) began in 1998 with a pre-construction load test program. This $1.2 billion design-build project consists of approximately 13 kilometers of elevated twin rail. The elevated rail system is supported on nearly 500 piers requiring deep foundations. The presence of underlying compressible and liquefiable soils as well as space constraints precluded the use of large spread footings. In the 1980's the Port Authority undertook extensive testing to evaluate various piles and drilled shafts types. The LRS piling sub-contractor and the Geotechnical Engineer conducted additional tests for this project to identify the most cost effective deep foundation type. Candidate piles types included: Monotube®, Tapertube®, and closed ended pipe piles. The tapered pile types were found to be the most cost effective and the project utilized both the Monotube® and Tapertube® piles. This paper presents the results of the load test program and the issues related to pile driving induced vibrations and ground movement.